Chemical composition of ferromanganese nodules and crusts from the Pacific using atomic absorption analysis - D Pasho (PANGAEA, 2023)
Manganese nodules were retrieved during cruise TOWMAS of the R/V Thomas Washington from Scripps Oceanographic Institution (SIO). Their chemical composition was determined using atomic absorption spectrophotometry.